Growth Strategies for Africa - Collier, Paul (World Bank, Washington, DC, 2017)
Over the past four decades Africa has diverged from other developing regions and is now the poorest region in the world. This paper offers an explanation of Africa's slow growth in terms of its distinctive economic and human geography: its high dependence upon natural resource exports, the many landlocked countries, and the high ethnic diversity of the typical state. It discusses how key economic policy choices, especially trade and fiscal policy, and assistance from the international community, need to tailored specifically to these distinctive circumstances. Part one of this paper sets out an explanation for why this happened and whether it is likely to recur, using the building blocks of economic geography. Africa is distinctive both in its physical geography and its human geography and these have shaped its opportunities. Part one has three sections. Section two considers the implications of Africa's distinctive physical geography. It accounts for some of Africa's slow growth and suggests how strategies will need to differ radically among Africa's countries. In section three author turn to its distinctive human geography and the political problems that this has created. To a considerable extent these problems recently have been surmounted: Africa's human geography may explain delayed take-off rather than predict persistent stagnation. Finally, in section four, author consider three interactions between physical geography and human geography that generate intractable problems that are likely to require both regional action and international assistance in various forms. Part two uses the analysis of part one to consider policy options. Section five discusses options for African governments. Section six focuses on the supporting actions that can be taken by governments outside Africa and by international agencies. Section seven offers a brief conclusion.